Level of E-Report Utilization in Special Region of Yogyakarta: Layne and Lee Model Perspective - Iqbal, Muhammad; Pribadi, Ulung (Journal of Community Development Research (Humanities and Social Sciences), 2020)
This article will analyze the Level of E-Report Utilization in the Special Region of Yogyakarta using Layne and Lee’s theory. Special Region of Yogyakarta has developed the use of e-government in each district and city in the Special Region of Yogyakarta. The development of e-government in the Special Region of Yogyakarta is related to the development of Jogja Cyber Province in Yogyakarta. One form of implementation of E-Government in DIY is E-Report in each regencies and city. Gunungkidul and Kulon Progo districts do not yet have an online community-based complaint system specifically for their communities. Gunungkidul Regency and Kulon Progo Regency still rely on email, social media, the official government website, and the SMS Center to interact with their communities. In addition to Gunungkidul Regency and Kulon Progo Regency, other local governments in DIY have specifically provided E-Report for their communities. This research is a qualitative research descriptive, which is done to describe the problem being researched and objectively integrating data at the research site. The type of data used in this study is secondary data. Based on the theory of Dimensions and Stages of e-Government Development theory developed by Layne and Lee shows that Kulon Progo Regency and Gunungkidul Regency are at the level of Vertical Integration. Furthermore, the Yogyakarta City, Sleman Regency and Bantul Regency have been at the highest level, namely at the Horizontal Integration level. Keywords: E-Government, E-Report, Online Government, Cyber Government, Special Region of Yogyakarta